Injury prevention programs in youth: A narrative review targeting females. - Sommerfield, L.; Harrison, C. B.; Whatman, C.; Maulder, P. S. (Strength and Conditioning Journal, 2020)
Injury prevention (IP) programs have been developed to reduce sports-related injuries and risk factors for injuries and to improve athletic performance in youth. This review aims to provide an overview of IP programs in youth females, males, and both sexes and then provide recommendations for those working with female athletes. Independent IP training programs with a high session attendance, of greater than 20 minutes in length, and completed 2-3 times per week have shown the greatest benefit. In addition, programs with multiple components, progressed according to the technical competency of the participants, are the most beneficial. For a video abstract of this article, see Supplemental Digital Content 1, http://links.lww.com/scj/A261.